“Old soldiers need only apply”: Exploring Pathways to the Quasi-Civilianisation of the Maritime Sector in Indonesia - Agastia, I Gusti Bagus Dharma (UI Scholars Hub, 2024)
This article explores the phenomenon of quasi-civilianisation, or the inclusion of former or active-duty military officers in civilian administrative positions, in maritime security governance in Indonesia. To what extent is the maritime sector quasi-civilianised? Second, what are the pathways to quasi-civilianisation in the maritime sector? This paper finds that quasi-civilians tend to be concentrated in paramilitary agencies and to a lesser extent, in limited functional roles within the civilian administration. Quasi-civilians are desirable for these positions due to their expertise and ability to mediate between military and civilian counterparts. Moreover, the appointment of quasi-civilians has generally complied with prevailing regulations preserving civilian control. This paper represents an exploratory attempt at advancing the discussion of quasi-civilianisation by exploring the phenomenon in the maritime sector in post-authoritarian Indonesia.